Curcumin and α/β-Adrenergic Antagonists Cotreatment Reverse Liver Cirrhosis in Hamsters: Participation of Nrf-2 and NF-κB - José Roberto Macías-Pérez; Bruno Jesús Vázquez-López; Martin Humberto Muñoz-Ortega; Liseth Rubí Aldaba-Muruato; Sandra Luz Martínez-Hernández; Esperanza Sánchez-Alemán; Javier Ventura-Juárez (Journal of Immunology Research)
Liver cirrhosis is the result of an uncontrolled fibrogenetic process, due to the activation and subsequent differentiation into myofibroblasts of the hepatic stellate cells (HSC). It is known that HSC express adrenoreceptors (AR), and the use of AR antagonists protects experimental animals from cirrhosis. However, several studies suggest that the toxicity generated by metabolism of these antagonists would hinder its use in cirrhotic patients. In addition, liver fibrosis may be associated with a decrease of the antioxidant response of the nuclear factor erythroid 2-related factor 2 (Nrf-2) and the overregulation of the proinflammatory pathway of nuclear factor kappa B (NF-κB). Therefore, in the present work, the capacity of doxazosin (α1 antagonist), carvedilol (nonselective beta-adrenoceptor blocker with alpha 1-blocking properties), and curcumin (antioxidant and anti-inflammatory compound) to reverse liver cirrhosis and studying the possible modulation of Nrf-2 and NF-κB were evaluated. Hamsters received CCl4 for 20 weeks, and then treatments were immediately administered for 4 weeks more. The individual administration of doxazosin or carvedilol showed less ability to reverse cirrhosis in relation to concomitantly curcumin administration. However, the best effect was the combined effect of doxazosin, carvedilol, and curcumin, reversing liver fibrosis and decreasing the amount of collagen I (Sirius red stain) without affecting the morphology of hepatocytes (hematoxylin and eosin stain), showing normal hepatic function (glucose, albumin, AST, ALT, total bilirubin, and total proteins). In addition, carvedilol treatment and the combination of doxazosin with curcumin increased Nrf-2/NF-κB mRNA ratio and its protein expression in the inflammatory cells in the livers, possibly as another mechanism of hepatoprotection. Therefore, these results suggest for the first time that α/β adrenergic blockers with curcumin completely reverse hepatic damage, possibly as a result of adrenergic antagonism on HSC and conceivably by the increase of Nrf-2/NF-κB mRNA ratio.